1958
DOI: 10.1152/ajplegacy.1958.192.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Renal Citric Acid Utilization in the Dog

Abstract: The renal uptake, metabolism and excretion of endogenous and exogenous citrate have been determined in unilaterally nephrectomized London cannula preparations with and without the presence of the thyroparathyroid apparatus. The uptake of citrate by the kidney is related to total renal plasma flow and consistently exceeds the extraction of creatinine. Only a small fraction of endogenous citrate removed from the blood passing though the kidney is excreted in the urine. The capacity of the kidney to metabolize ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1961
1961
1994
1994

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The hypothesis that citrate metabolism in the renal tubular cell is closely related to urinary citrate excretion is particularly attractive because of the known avidity of the kidney for the blood citrate (19,20) and because of the demonstrated rapid metabolism of citrate by kidney tissue (13). The present experiments conclusively demonstrate an effect of acidosis and alkalosis on renal clearance of plasma citrate.…”
Section: Discussionsupporting
confidence: 61%
“…The hypothesis that citrate metabolism in the renal tubular cell is closely related to urinary citrate excretion is particularly attractive because of the known avidity of the kidney for the blood citrate (19,20) and because of the demonstrated rapid metabolism of citrate by kidney tissue (13). The present experiments conclusively demonstrate an effect of acidosis and alkalosis on renal clearance of plasma citrate.…”
Section: Discussionsupporting
confidence: 61%
“…In vivo studies have indicated a considerable uptake of citrate by the liver (1) and kidney (2), and a release of citrate into the blood by the peripheral tissues (1,3) and intestine (4,5). Interest in the blood citrate flux has centered primarily around the importance of this intermediate in carbohydrate metabolism, in its relationship to calcium mobilization and deposition in bone (6), and in its role as a chelating agent for calcium in the urine (7,8).…”
mentioning
confidence: 99%
“…The mechanisms controlling renal citrate disposal are ill defined but acid-base balance, active reabsorption, or other causes could be invoked. The kidney is also particularly active in citrate synthesis (Orten and Smith 1939) and utilization (Herndon and Freeman 1958). Possibly trans-aconitate may preferentially accumulate in renal tubular cells and cause enhanced aconitase inhibition there.…”
Section: Discussionmentioning
confidence: 99%